Analisis faktor-faktor yang berhubungan dengan pemanfaatan pelayanan pos bina terpadu penyakit tidak menular - Sari, Ni Putu Sri Wulan; Akbar, Izaak Zoelkarnain; Panghiyangani, Roselina; Musafaah, Musafaah; Shadiqi, Muhammad Abdan (Holistik Jurnal Kesehatan, 2025)
Background: Non-communicable diseases (NCDs) continue to increase and become a global health problem, including in Indonesia. Integrated development post for non-communicable diseases was developed to detect and control NCD risk factors early. However, the utilization of community health center Cempaka Banjarbaru has decreased, from 12.18% in 2022 to 10.17% in 2023 and is still far from the 70% target. Low utilization of non-communicable disease integrated service centers can increase non-communicable disease rates and burden community health center budgets, as well as affect the achievement of minimum service standards (MSS). Purpose: To analyze the factors associated with the utilization of integrated development post for non-communicable diseases services.   Method: This study used a quantitative approach with a cross-sectional design. The population of this study were people aged 18-59 years in the community health center Cempaka Banjarbaru working area. The sample was taken using stratified random sampling technique with a total of 110 respondents. Data collection was done through distributing questionnaires that had been tested for validity and reliability. Data were analyzed using univariate analysis, bivariate using chi-square test, and multivariate using multiple logistic regression test. Results: The chi-square test showed that the knowledge variable had a p value = 0.0001 (<0.05) and PR = 1.851, employment status p value = 0.014 (<0.05) and PR = 1.580, distance traveled had a p value = 1.000 (>0.05) and PR = 1.012, family support had a p value = 0.0001 (<0.05) and PR = 2.847, and ease of obtaining information had a p value = 0.0001 (<0.05) and PR = 1.655. This means that there is a relationship between knowledge, employment status, family support, and ease of obtaining information with the utilization of integrated service center for non-communicable diseases services. However, the travel distance variable was not associated with the utilization of integrated service center for non-communicable diseases services. Based on multiple linear regression tests, the family support variable is the most dominant variable associated with the utilization of integrated service center for non-communicable diseases services with an EXP B value of 34,108. Conclusion: This study showed that knowledge, employment status, family support, and ease of obtaining information were associated with the utilization of integrated service center for non-communicable diseases, with family support as the dominant factor. Meanwhile, travel distance was not associated with the utilization of integrated service center for non-communicable diseases. Suggestion: The community is expected to make more use of an integrated service center for non-communicable diseases, while the community health center needs to organize regular counseling, with various media to increase understanding about health.   Keywords: Integrated Development Post; Non-communicable Diseases (NCDs); Risk Factors; Services.   Pendahuluan: Penyakit tidak menular (PTM) terus meningkat dan menjadi masalah kesehatan global, termasuk di Indonesia.  Posbindu PTM dikembangkan untuk mendeteksi dini dan mengendalikan faktor risiko PTM. Namun, pemanfaatan di Puskesmas Rawat Inap Cempaka Banjarbaru mengalami penurunan, yaitu 12.18% pada 2022 menjadi 10.17% pada 2023 dan masih jauh dari target 70%. Rendahnya pemanfaatan posbindu PTM dapat meningkatkan angka penyakit tidak menular dan membebani anggaran kesehatan puskesmas, serta memengaruhi capaian standar pelayanan minimal (SPM). Tujuan: Untuk menganalisis faktor-faktor yang berhubungan dengan pemanfaatan pelayanan pos bina terpadu penyakit tidak menular. Metode: Penelitian kuantitatif dengan desain cross sectional. Populasi penelitian ini adalah berusia 18-59 tahun di wilayah kerja Puskesmas Rawat Inap Cempaka. Sampel diambil dengan teknik stratified random sampling dengan jumlah responden sebanyak 110. Pengumpulan data melalui penyebaran kuesioner yang telah diuji validitas dan reliabilitasnya. Analisis data menggunakan analisis univariat, bivariat menggunakan uji chi-square, dan multivariat menggunakan uji regresi logistik berganda. Hasil: Uji chi-square menunjukkan variabel pengetahuan memiliki nilai p= 0.0001 (< 0.05) dan PR = 1.851, status pekerjaan nilai p = 0.014 (< 0.05) dan PR = 1.580, jarak tempuh memiliki nilai p = 1.000 (> 0.05) dan PR = 1.012, dukungan keluarga memiliki nilai p = 0.0001 (< 0.05) dan PR = 2.847, serta kemudahan memperoleh informasi memiliki nilai p = 0.0001 (< 0.05) dan PR = 1.655. Hal ini menunjukkan adanya hubungan antara pengetahuan, status pekerjaan, dukungan keluarga, dan kemudahan memperoleh informasi dengan pemanfaatan pelayanan Posbindu PTM. Namun, variabel jarak tempuh tidak berhubungan dengan pemanfaatan posbindu PTM tersebut. Berdasarkan uji regresi linier berganda, variabel dukungan keluarga menjadi variabel yang paling dominan berkaitan dengan pemanfaatan pelayanan posbindu PTM dengan nilai EXP B sebesar 34.108. Simpulan: Pengetahuan, status pekerjaan, dukungan keluarga, dan kemudahan memperoleh informasi berhubungan dengan pemanfaatan posbindu PTM, dengan dukungan keluarga sebagai faktor dominan. Sementara itu, jarak tempuh tidak berhubungan dengan pemanfaatan posbindu PTM. Saran: Masyarakat diharapkan dapat lebih memanfaatkan posbindu PTM, sementara puskesmas perlu menyelenggarakan penyuluhan berkala, dengan berbagai media untuk meningkatkan pemahaman tentang kesehatan.   Kata Kunci: Faktor Risiko; Pelayanan; Penyakit Tidak Menular (PTM); Pos Pembinaan Terpadu (Posbindu).